The Capture of the Ship Ayios Ioannis Theologos in the Summer of 1825: An Investigation of Limits - Dimitropoulos, Dimitris (Historein, 2022)
The Greek Revolution detached a part of the territory of the Ottoman Empire and structured a newly founded state, which rearranged the balance among and the roles of the people and reshaped the boundaries between legal and illegal in international transactions, social relations and financial endeavours. This article describes an incident that took place in 1825 in the Aegean concerning the capture and the plundering of a commercial ship sailing under a Russian flag by raiders from Psara. It explores the boundaries in the actions, function and role of the protagonists of this episode. The following groups are examined as examples of people, groups and statuses: the raiders who operated on the borderline of piracy and privateering (corso); the shipowner, who was at the same time a captain and entrepreneur; the crew of the ship, who were seamen and traders; the Greek local authorities, who maintained a balance between national interest, local interest and self-interest; and the consuls, who were experiencing their twilight before the essential end of the role they enjoyed in the context of the Ottoman Empire.